Newly deposited atmospheric mercury in a simulated rice ecosystem in an active mercury mining region: High loading, accumulation, and availability. (January 2020) - Ao, Ming; Xu, Xiaohang; Wu, Yonggui; Zhang, Chao; Meng, Bo; Shang, Lihai; Liang, Longchao; Qiu, Rongliang; Wang, Shizhong; Qian, Xiaoli; Zhao, Lei; Qiu, Guangle
Abstract: Mercury (Hg) mining activities are an important anthropogenic source of atmospheric Hg. The Xunyang Hg mine located in Shaanxi Province is the largest active Hg producing centre in China. To understand the biogeochemical processes of atmospheric Hg through Hg mining activities, six groups of experimental pots were carefully designed to investigate the effect of Hg mining activities on Hg contamination from atmospheric deposition in the local surface soils. Based on the variations of Hg in the soil from the experimental pots, the deposition flux and loading of Hg in the Xunyang Hg mining district were investigated. The results showed that the average concentration of total gaseous mercury (TGM) as high as 193 ± 122 ng m −3 was observed in the ambient air, which was orders of magnitude higher than that in remote areas. The average deposition flux and annual loading of atmospheric Hg were 72 mg m −2 y −1 and 10 t y −1, respectively. The dominant atmospheric Hg deposition is within a distance range of 6.0–12 km from the Hg retorting facility, accounting for approximately 85% of the total Hg loading. After 14 months of exposure, total mercury (THg) concentrations in the soil from the experimental pots increased 0.35–9.5 times, and the highest concentrations of methylmercury (MeHg) (3.7 ± 2.9 μg kg −1 ) in soil were observed in February. Concentrations as high as 643 μg kg −1 THg and 13 μg kg −1 MeHg in rice were observed in the second experimental year. Elevated concentrations of both THg and MeHg in rice indicated that the newly deposited atmospheric Hg was bioavailable, readily methylated, and taken up by rice, suggesting that the ongoing Hg mining activities cause serious Hg contamination in the soil-rice ecosystem and posed a threat to local residents in the Xunyang Hg mining area. Graphical abstract: Image 1 Highlights: Cinnabar retorting causes significant Hg emissions into the surrounding environment. Approximately 85% of the TGM emitted from the Hg smelter is deposited within a distance of 6.0–12 km. The newly deposited TGM is bioavailable, readily methylated, and easily taken up by rice.